Efektifitas Penerapan Media Jigsaw Puzzle terhadap Minat Belajar Peserta Didik Kelas V Madrasah Ibtidaiah - Maghfirotun, Khubni; Sari, Mukaromah Lilya (FAKULTAS AGAMA ISLAM UNIVERSITAS BILLFATH, 2022)
This study aims to determine the learning students' interest of Class V MI Islmaiyah Bumiayu Baureno before implementing Jigsaw Puzzle in Fiqh learning; to recognize the interest after the application of Jigsaw puzzle media; to determine the effectiveness of Jigsaw puzzle media on learning interest. This research was a quantitative research through experimental methods (one group design) and carried out at MI Islamiyah Bumiayu students' attention, interest, thoughts and feelings ollected by random sampling. This study contained an independent variable, namely Jigsaw puzzle media while the dependent variable was the students interest. Data collection methods used questionnaires and observation. Validity test was analyzed using SPPSS version 25 as well as reliability test and data analysis techniques used percentage descriptive analysis. The normality test used table on-sample on SPSS version 25, as well as the Homogeneity test. Hypothesis analysis used T-test in SPSS version 25. Based on the result data analysis of the study, the students interest before the application of Jigsaw puzzle media showed in the low category with a percentage value of 60% and the acquisition of an average value of 50,80. Besides, after the application andia showed at a very high category in the number category value 84-100 was 76% with the acquisition of the average value of 86,28. Thus, this media is effective in increasing the students' interest in learning, with the values of one sample t test results were Tcount > Ttable and 55,39 > 2,06.